The Ideals of Harmony in Dualism in Tambo Alam Minangkabau - - Hendro; Silvia Rosa; - Sulastri; Wahyudi Rahmat (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2022)
Tambo is a historical literary work that contains the origins of the ancestors and customs of the Minangkabau people. One of the important themes in the Tambo is the division of two systems of government in Minangkabau customs called Lareh Nan Duo, which is full of symbolic language. This study aims to dismantle the meaning of Tambo which is required by the symbolic and ideological language. Roland Barthes' semiological theory is used to uncover the symbolic meaning behind the story of Lareh Nan Duo. This research is a qualitative study with a qualitative descriptive method. The data obtained is through a literature study. The research object material is sourced from Tambo text by Datoek Batoeah Sango (1959). The units of data analysis in this research are words, sentences, phrases, paragraphs, and discourses that tell about Lareh Nan Duo. The results of the analysis illustrate that the Minangkabau society is a dualistic society, divided by two systems of government and their rules. The journey of the Minangkabau people on the dualism of the system and the rules gave a sign that the Minangkabau people held to two truths. The Minangkabau people reduce them to a map, namely Islam. The Minangkabau people make Islam as harmonization in a prolonged dualism. This research can add to the treasures and become a reference for researchers in the field of Barthes’s Semiology which is applied to Tambo. This research opens up space for other researchers to get involved in the historiography